Indolic Structure Metabolites as Potential Biomarkers of Non-infectious Diseases - Beloborodova, Natalia V.; Chernevskaya, Ekaterina A.; Getsina, Maria L. (Current Pharmaceutical Design, 2021)
Interest in indolic structure metabolites, including a number of products of microbial biotransformation of the aromatic amino acid tryptophan, is increasingly growing. The review prepared by a team of authors is based on in-depthscrutiny of data available in PubMed, Scopus, Cyberleninka, Clinical Trials, and Cochrane Library, eventually narrowing the search to a set of keywords such as tryptophan metabolites; plasma metabolomics profiling; metabolomics fingerprinting; gas-, liquid chromatography mass spectrometry; serotonin; melatonin; tryptamine; indoxyl sulfate; indole-3-acetic acid; indole-3-propionic acid; 5-hydroxyindole-3-acetic acid; gut microbiota and microbial metabolites. It provides a summary that outlines the pattern of changes in the level of indolic structure metabolites in a number of diseases and deals with the data from the field of human microbiota metabolites. In modern experimental studies, including the use of gnotobiological (germ-free) animals, it has been convincingly proved that the formation of tryptophan metabolites such as indole-3-acetic acid, indole-3-propionic acid, tryptamine, and indoxyl sulfate is associated with gut bacteria. Attention to some concentration changes of indolic compounds is due to the fact that pronounced deviations and a significant decrease of these metabolites in the blood were found in a number of serious cardiovascular, brain or gastrointestinal diseases. The literature-based analysis allowed the authors to conclude that a constant (normal) level of the main metabolites of the indolic structure in the human body is maintained by a few strict anaerobic bacteria from the gut of a healthy body belonging to the species of Clostridium, Bacteroides, Peptostreptococcus, Eubacteria, etc. The authors focus on several metabolites of the indolic structure that can be called clinically significant in certain diseases, such as schizophrenia, depression, atherosclerosis, colorectal cancer, etc. Determining the level of indole metabolites in the blood can be used to diagnose and monitor the effectiveness of a comprehensive treatment approach.
Keywords: gut anaerobic bacteria